De novo SNP calling reveals the genetic differentiation and morphological divergence in genus Amaranthus. Issue 2 (25th April 2022) - Lin, Ya‐Ping; Wu, Tien‐Hor; Chan, Yan‐Kuang; van Zonneveld, Maarten; Schafleitner, Roland
Abstract: Amaranth species ( Amaranthus spp.) serve as pseudo cereals and also as traditional leafy vegetables worldwide. In addition to high vigor and richness in nutrients, drought and salinity tolerance makes amaranth a promising vegetable to acclimatize to the effects of global climate change. The World Vegetable Center gene bank conserves ∼1, 000 amaranth accessions, and various agronomic properties of these accessions were recorded during seed regeneration over decades. In this study, we verified the taxonomic annotation of the germplasm based on a 15K single‐nucleotide polymorphism (SNP) set. Given that the yield components of grain amaranth are different from those of leaf amaranth, we observed that grain amaranth species presented larger inflorescences and earlier flowering than leaf amaranth species. Dual‐purpose amaranth showed larger leaves than leaf amaranth and later flowering than grain amaranth, which seemed reasonable because farmers can harvest more leaves during the prolonged vegetable stage, which also provides recovery time to enrich grain production. Considering frequent interspecific hybridization among species of the grain amaranth complex, we performed an interspecific genome‐wide association study (GWAS) for days to flowering, identifying a AGL20 / SOC1 homolog. Another GWAS using only A. tricolor L. accessions revealed six candidate genes homologous to lba1, bri1, sgs1, and fca . These homologous genes were involved in the regulation of flowering time in Arabidopsis thaliana (L.) Heynh. This study revealed the usefulness of genotypic data for species demarcation in the genus Amaranthus and the potential of interspecific GWAS to detect quantitative trait loci (QTL) across different species, opening up the possibility of targeted introduction of specific genetic variants into different Amaranthus species. Core Ideas: De novo single‐nucleotide polymorphism calling is able to reduce unmapped reads across multiple species. Amaranthus species can be clarified through genotypes. Phenotypic divergence reflects domestication of crop for different purposes. Genome‐wide association study reveals candidate genes for flowering time among different‐purpose amaranth species.